Navigating power imbalances in landscape governance: a network and influence analysis in southern Zambia - Siangulube, F.S.; Ros-Tonen, M.A.F.; Reed, J.; Djoudi, H.; Gumbo, D.; Sunderland, T.C.H. (Springer, 2023)
Actors engaging in integrated landscape approaches to reconciling conservation and development represent multiple sectors and scales and actors with different powers, resource access, and influence on decision-making. Despite growing acknowledgement, limited evidence exists on the implications of power relations for landscape governance. Therefore, this paper asks why and how different forms of power unfold and affect the functioning of multi-stakeholder platforms in southern Zambia. Social network analysis and a power influence assessment reveal that all actors exercise some form of visible, hidden, or invisible power in different social spaces to influence decision-making or negotiate a new social order. The intersection of customary and state governance reveals that power imbalances are the product of actors’ social belongingness, situatedness, and settlement histories. We conclude that integrated landscape approaches are potentially suited to balance power by triggering new dynamic social spaces for different power holders to engage in landscape decision-making. However, a power analysis before implementing a landscape approach helps better recognise power differentials and create a basis for marginalised actors to participate in decision-making equally. The paper bears relevance beyond the case, as the methods used to unravel power dynamics in contested landscapes are applicable across the tropics where mixed statutory and customary governance arrangements prevail.